2000
DOI: 10.1046/j.1469-0705.2000.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound in the evaluation of fetal anomalies

Abstract: The 3D US offered diagnostic advantages in about one-half of the selected cases studied and had effect on patient management in 5% of cases. This modality can be a powerful adjunctive tool to 2D US in providing a more comprehensible, 3D US impression of congenital anomalies. Thus, 3D US is currently most helpful as a targeted study complementing 2D US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0
4

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 23 publications
3
74
0
4
Order By: Relevance
“…Three-dimensional ultrasonography was thought to be "most helpful" for localizing bony defects in 10 fetuses with spina bifida. 9 One of their cases involved a spinal defect that could not be imaged by 2DUS because of fetal position. The precise level of the defect was determined by endovaginal 3DUS by allowing reconstruction of appropriate planar images from volume data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional ultrasonography was thought to be "most helpful" for localizing bony defects in 10 fetuses with spina bifida. 9 One of their cases involved a spinal defect that could not be imaged by 2DUS because of fetal position. The precise level of the defect was determined by endovaginal 3DUS by allowing reconstruction of appropriate planar images from volume data.…”
mentioning
confidence: 99%
“…Several investigators have also suggested that three-dimensional ultrasonography (3DUS) can be used to evaluate this condition. [6][7][8][9][10] Johnson and coworkers 8 have already described the use of rendered spine images as a reference for position on threedimensional (3D) multiplanar views. Only 5 of their cases, however, compared prenatal findings with the vertebral defect level after delivery.…”
mentioning
confidence: 99%
“…Dyson et al 8 described the clinical impact of 3-dimensional (3D) sonographic imaging of fetal anomalies compared with conventional 2-dimensional (2D) sonography and concluded that 3D sonography was superior to 2D sonography by providing more comprehensive images of congenital anomalies. In many recent studies, 3D sonography consistently displayed facial anomalies with greater accuracy and clarity than 2D sonography.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies reported on the technical and clinical advantages afforded by 3D sonography in obstetric imaging. [12][13][14] Despite these obvious advantages of volume sonography, this modality has not yet attained wide acceptance in obstetric imaging. A major hurdle limiting the wide applicability of 3D sonography in clinical practice is its steep learning curve.…”
Section: Discussionmentioning
confidence: 99%